Anticipatory postural adjustments during sitting reach movement in post-stroke subjects - Pereira, Soraia (2014)
The study assessed the effect of velocity of arm movement on the generation of APAs in the contralateral and ipsilateral muscles of individuals with stroke in the sitting position. In the sitting position, 10 healthy and 8 post-stroke subjects reached for an object placed at the scapular plane and mid-sternum height at self-selected and fast velocities. Electromyography was recorded from the anterior deltoid (AD), upper (UT) and lower trapezius (LT), and latissimus dorsi (LD). Kinematic analysis was used to assess peak velocity and trunk displacement. Post-stroke subjects presented a delay of APAs on both sides of the body compared to healthy subjects. Differences were found between the timing of APAs on the ipsilateral and contralateral LD and LT in both movement speeds and in the ipsilateral UT during movement of the non-affected arm at a self-selected velocity. A delay in the contralateral LD in the reaching movement with the non-affected arm at fast velocity was also observed. Trunk displacement was greater in post-stroke subjects. In the sitting position, APAs were delayed in both fast and self-selected movements on both sides in post-stroke subjects, which also presented a higher trunk displacement.